2011
DOI: 10.1542/peds.2010-2284
|View full text |Cite
|
Sign up to set email alerts
|

Parental Understanding of Newborn Screening for Cystic Fibrosis After a Negative Sweat-Test

Abstract: Parental knowledge about CF is high, but confusion about the child's carrier status and the concept of residual risk persist despite genetic counseling. Relatives express low interest in carrier testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 27 publications
3
53
0
Order By: Relevance
“…Our results confirm the results of a recent non-controlled study showing that the early anxiety in parents induced by a positive screening result for CF was mostly decreased within three months thereafter, or that parents were reassured after genetic counseling and sweat test results [14]. The results after one and two years did not differ significantly [5].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results confirm the results of a recent non-controlled study showing that the early anxiety in parents induced by a positive screening result for CF was mostly decreased within three months thereafter, or that parents were reassured after genetic counseling and sweat test results [14]. The results after one and two years did not differ significantly [5].…”
Section: Discussionsupporting
confidence: 89%
“…Very few studies report on internet as an information source for parents about NBS [14], [15], [16]. Two studies showed that half respectively 82% of the parents use internet after a positive screening result to look for additional information, which is comparable to our study (69%) [16].…”
Section: Discussionsupporting
confidence: 83%
“…The concept of “carrier status” can be confusing for parents to understand and primary care providers' (PCPs') communication of these results has been criticized 7-14 . These challenges can lead to the development of parental psychosocial complications such as depression, anxiety, fear, and confusion 14-21 .…”
Section: Introductionmentioning
confidence: 99%
“…The concept of "carrier status" can be confusing for parents to understand and primary care providers' (PCPs') communication of these results has been criticized [7][8][9][10][11][12][13][14] . These challenges can lead to the development of parental psychosocial complications such as depression, anxiety, fear, and confusion [14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…These challenges can lead to the development of parental psychosocial complications such as depression, anxiety, fear, and confusion [14][15][16][17][18][19][20][21] . We contend that these consequences are potentially avoidable or alleviated by providing access to follow-up and informational resources.…”
Section: Introductionmentioning
confidence: 99%